Pengelolaan Supervisi Klinis Pada Sekolah Dasar Negeri 01 Gantiwarno - Suprapti., Suprapti; , Dr. Sabar Narimo, M.M., M.Pd; , Dr. Sofyan Anif, M.Si (2016)
The purpose of this study describes the management of clinical supervision on SD Negeri 01 Gantiwarno, Matesih, Karanganyar. The purpose of the research consisted of three which describe management planning, implementation and feedback clinical supervision. Qualitative research methods using ethnographic design. The research location in SD Negeri 01 Gantiwarno. Informant research was superintendent, principals and classroom teachers. The data collection technique was direct observation, interviews, and documentation. Data analysis techniques through the four stages of data collection, data reduction, data presentation, and conclusion. Validation data using credibility, transferability, validity and confirmability. Research results achieved include 1) planning by assessing the performance of the administration in the form of lesson planning. Administration of structured learning good shows teachers are performing well, 2) the implementation of learning through observation. PAIKEM learning activities for the achievement of teacher performance, 3) feedback is carried out individually and in groups. The activities include evaluation of the main tasks, functions, and performance assessment. Professional teachers are teachers who have minimal performance appraisal well